LITERATUR REVIEW: TRIKIASIS - Gerliandi, Egi Oktarian; Mustofa, Syazili; Lisiswanti, Rika; Sukohar, Asep (CV. Jasa Sukses Abadi, 2024)
Trichiasis is a pathological disorder characterized by the abnormal growth of eyelashes towards the eyeball, resulting in irritation, pain, and potential harm to the eye. This research utilizes a method of sear Trichiasis is a pathological disorder characterized by the abnormal growth of eyelashes towards the eyeball, resulting in irritation, pain, and potential harm to the eye. The pathophysiology of trichiasis originates with alterations in the structure of the eyelashes and eyelids. Trichiasis is classified into six categories according to the source and location of abnormal eyelash development. The clinical presentation of trichiasis differs according on the extent of the condition. Trichiasis can be diagnosed by assessing the patient's medical history and doing a thorough physical examination. The history encompasses the patient's medical background, record of medication usage, past eye surgical procedures, and the patient's reported symptoms. The physical examination encompasses assessments of visual acuity, biomicroscopic inspection, evaluation of eyelid margins, and the administration of the Schirmer test. The treatment for trichiasis is determined by the extent of eyelash involvement, which includes factors such as the Soft Contact Lense Base Curve. Treatment options may include eyelash removal and surgical procedures, depending on the specific form of trichiasis that the patient is suffering. ching for articles on Google Scholar, PubMed, and NCBI. The search is limited to a specific year range determined by the researcher. The search is conducted using keywords such as trichiasis, etiology of trichiasis, pathophysiology of trichiasis, classification of trichiasis, clinical manifestations of trichiasis, diagnosis of trichiasis, and management of trichiasis. The study's findings revealed that the cause of trichiasis remained unknown, however it was hypothesized to be a result of infection. The pathophysiology of trichiasis originates with alterations in the structure of the eyelashes and eyelids. Trichiasis is classified into six categories according to the source and location of abnormal eyelash development. The clinical presentation of trichiasis differs according on the extent of the condition. Trichiasis can be diagnosed by assessing the patient's medical history and doing a thorough physical examination. The history encompasses the patient's medical background, record of medication usage, past eye surgical procedures, and the patient's reported symptoms. The physical examination encompasses assessments of visual acuity, biomicroscopic inspection, evaluation of eyelid margins, and the administration of the Schirmer test. The treatment for trichiasis is determined by the extent of eyelash involvement, which includes factors such as the Soft Contact Lense Base Curve. Treatment options may include eyelash removal and surgical procedures, depending on the specific form of trichiasis that the patient is suffering.